2019
DOI: 10.1101/531194
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pure tones modulate the representation of orientation and direction in the primary visual cortex

Abstract: Multimodal sensory integration facilitates the generation of a unified and coherent perception of the environment. It is now well established that unimodal sensory perceptions, such as vision, are improved in multisensory contexts. While multimodal integration is primarily performed by dedicated multisensory brain regions such as the association cortices or the superior colliculus, recent studies have shown that multisensory interactions also occur in primary sensory cortices. In particular, sounds were shown … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 42 publications
4
35
0
Order By: Relevance
“…SOM + interneurons, on the other hand, could follow a non-Hebbian plasticity rule (e.g., anti-Hebbian or homeostatic), which results in a nonselective connectivity ( Wilson et al, 2012 ). Our second hypothesis posits that changes in the activity of inhibitory neurons are responsible for the highly variable receptive fields observed in recent experiments ( Bathellier et al, 2012 ; Ruff and Cohen, 2014 , 2019 ; Benjamin et al, 2019 ; Billeh et al, 2019 ; McClure and Polack, 2019 ) ( Fig. 1 C ).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…SOM + interneurons, on the other hand, could follow a non-Hebbian plasticity rule (e.g., anti-Hebbian or homeostatic), which results in a nonselective connectivity ( Wilson et al, 2012 ). Our second hypothesis posits that changes in the activity of inhibitory neurons are responsible for the highly variable receptive fields observed in recent experiments ( Bathellier et al, 2012 ; Ruff and Cohen, 2014 , 2019 ; Benjamin et al, 2019 ; Billeh et al, 2019 ; McClure and Polack, 2019 ) ( Fig. 1 C ).…”
Section: Introductionmentioning
confidence: 89%
“…Finally, recent work by Billeh et al (2019) showed that, in mice, visual neurons change their response to the direction of motion of visual stimuli depending on either the temporal or the spatial frequency of the stimulus (drifting grating). These results suggest that receptive fields of sensory neurons are dramatically affected by input (i.e., contextual/attentional states) ( Fritz et al, 2003 ; Kohn and Movshon, 2004 ; Ruff and Cohen, 2014 , 2019 ; Benjamin et al, 2019 ; McClure and Polack, 2019 ), or different aspects of the sensory stimulus ( Bathellier et al, 2012 ; Billeh et al, 2019 ), but it is unclear by which mechanisms such changes can transpire.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The effect was attributed to an increase in the stochastic resonance. Support for this theory comes from Méndez-Balbuena et al (2015). The authors used a visual pattern reversal task and measured the visual evoked response, while introducing additional tactile noise and found an increase in the P100 amplitude through the noise.…”
Section: Time Since Tone Change (Ms)mentioning
confidence: 99%